Mentorship matters strategies and successes in Ob-Gyn residency training - Enriquez-Gamboa, Michelle; Nemuel S.Fajutagana, MD, MHPEd (2025)
The development of this OB-GYN mentorship program began with a comprehensive needs assessment, aimed at identifying residents' perceptions
and expectations regarding mentorship. The survey revealed a unanimous recognition of mentorship’s importance in supporting both personal and
professional growth. All respondents rated mentorship as either very or extremely important, especially in enhancing clinical confidence. However, limited faculty accessibility was noted as a challenge. Residents highlighted priority areas for mentoring: clinical skills development, career planning, research guidance, work-life balance, and personal well-being. There was also a strong preference for a blended mentoring format, incorporating one-on-one, group, and peer-to-peer interactions. Crucially, all residents expressed interest in participating in a formal mentoring program, indicating strong demand and institutional readiness. To prepare for the program’s implementation, a Mentoring Course was
conducted, facilitated by respected educators Professors Emely Dicolen and Monica Walet. This workshop equipped both mentors and mentees with foundational knowledge and practical skills in effective mentoring relationships. During the pilot implementation, mentees demonstrated positive outcomes, including improved confidence, increased clarity in career goals, and a greater sense of emotional support. The program fostered a more open and supportive environment within the department. A mentoring agreement— including a confidentiality clause—was signed by both mentors and mentees, formalizing the partnership. The mentoring program was designed using a needs-based approach, grounded in the principles of Appreciative Inquiry, ensuring that the process was collaborative, strengths-based, and responsive to the real-life context of OB-GYN
residents. This dynamic design supports continuous development throughout residency, from onboarding to graduation. Regular post-training sharing sessions have proven essential in sustaining interest and engagement in the mentoring program. These sessions—often informal in nature—have provided a valuable platform for both mentors and mentees to reflect on their experiences, share insights, and reinforce connections. Early feedback indicates that these informal interactions are not only helpful but also contribute positively to the overall mentoring culture. This ongoing exchange fosters a sense of community and support, which is critical in achieving long-term goals of the program, including reducing attrition rates among OB-GYN residents. While the pilot showed promising results, it also identified areas for further improvement. These include conducting Level 2 and Level 3 evaluations (measuring learning and behavioral changes), ensuring regular mentor-mentee interactions, and enhancing consistency in mentor engagement. Overall, the introduction of a structured mentoring program has proven to be a strategic and transformative intervention. Mentors served not only as clinical guides but also as role models, career advisors, and wellness advocates. The program significantly enhanced resident satisfaction, confidence, and clarity in professional pathways, while also serving as a buffer against burnout—one of the most pressing issues in medical training today.
Capstone project (MHPED, Professional Track)
print & pdf
Keywords: Mentoring; Mentorship; Residency training